The Use of Indigenous Knowledge in Squirrels Repellent: The Case of Coconut Farmer in Tumpat, Kelantan, Malaysia - Aweng E.R., Arham Muchtar A.B., M.A. Salam, Sharifah Aisyah S.O., Appalasamy A., M. Mazlan (International Journal of Advanced Science and Technology, 2020)
A large population in Tumpat, Kelantan, Malaysia belongs to the peasant community who work in vegetable and fruit farms including coconut farms. Squirrel is known to be the main pest of coconut fruit, often puncturing and eating coconut flesh as food and thus lowering the production in coconut farm. In order to control pest in coconut farm, the farmers in Tumpat have invented a non-destructive tool, a natural repellant. This repellent is created using natural and waste materials found around the farm. Basically, this device is a tap (kertuk) that has a knock rod and is powered by wind flow. The tap is similar (kertuk) to the wooden plank used by the people in the villages in the past to mark the time of prayer in mosque or to call the people for an important assembly. The device is made of bamboo and a short wooden stick is (one foot) fastened to a piece of string tied to both ends of the tap (kertuk). The knock rod is tied with a used fertilizer sack that acts as a blade and receives wind blows that eventually moves the knocker to knock the tap (kertuk). These three components are hung using a rope on a long pole stick and fastened to a coconut trunk. The generated sound alarms the squirrel and repels them from coconut fruit. This tap (kertuk) produces a loud sound each time the wind blows. The coconut plantation farmer’s indigenous knowledge on squirrel repellent technique however is fast disappearing as it remains in the custody of a few community elders and if not documented, it may soon disappear. This study aims to document this knowledge through informal conversational interview with farmer as well as by observing the working mechanism of this invention. Based on an interview and observation, this invention is effective in repelling squirrels from attacking the coconut fruit farm.